Effect of organizational culture on organizational performance: The case of security sector - Rodrigues, A.; Pereira, L.; Lopes da Costa, R.; Martins, L.; Gonçalves, R. (Book of abstracts da XI Postgraduate Conference Management, Hospitality & Tourism - ESGHT| ISCAL 2020, 2020)
Aims: Today’s business world is characterized by its constant rapidly changing environment, facing a very competitive economic context, making it crucial for the achievement of business success to understand, timely, what drives its results, namely its performance. Organizational performance may be affected by several number of variables and the understanding of these variables are decisive for business management. This research aims to address and measure organizational performance, understanding if and how much it is influenced by organizational culture, as well as if employee work engagement mediates the mentioned relationship. Methodology / Approach: We approach the concept of organizational culture and its evolution over time, ending up by specifically addressing it according to the competing values framework (Quinn & Rohrbaugh, 1983) and measuring it through the instrument “Focus Questionnaire” (Van Muijen et al., 1999). Organizational performance is conceptually introduced and its strategic importance to the general success of the company is duly framed. In order to assess organizational performance, we use a measurement instrument developed by Delaney and Huselid (1996). The literature evidences that employee work engagement effectively mediates the mentioned relationship, which within this framework we assess according to the Utrecht Work Engagement Scale (Schaufeli et al., 2002). The assessment of the referred tripartite influential relationship is accomplished through the formulation and testing of a research question, which is “Do organizational culture types influence organizational performance and is this influence mediated by employee work engagement?”, through the respective four sub research questions. For that purpose, we applied a questionnaire, composed by the three measurement instruments previously introduced, preceded by a pre-test procedure, to a sample composed by security professionals, receiving a total of 629 valid answers. Conclusions / Results: Our results evidence that culture positively and significantly influences both organizational performance and employee work engagement, which is aligned with the results of a variety of other researches on this topic, as well as that employee work engagement partially mediates the influence of all organizational culture types on organizational performance. Research implications: Managers who seek to achieve high levels of organizational performance shall understand and address organizational culture, being aware of the mediating effect that employee work engagement has on that influential relationship. Specifically considering a population composed by professionals that are responsible for the security of our organizations, it is critical to adapt the cultural context in which those individuals are inserted. As now known, clan culture, followed by hierarchy culture, are the cultural types that have a higher effect on organizational performance, being positively influenced by high levels of employee work engagement. Originality: This specific interactional relationship of organizational culture effect on organizational performance, mediated by employee work engagement, applied to this specific business sector, has never been address before.